2014
DOI: 10.4103/2277-9175.135158
|View full text |Cite
|
Sign up to set email alerts
|

Association of Epstein-Barr virus with invasive breast carcinoma and its impact on well-known clinicopathologic parameters in Iranian women

Abstract: Background:The association between Epstein-Barr virus (EBV) and breast carcinoma in Iranian women is uncertain. We examined EBV latent membrane protein-1 (LMP-1) antigen expression in breast carcinoma and its relationship with clinicopathologic parameters among a population of Iranian patients.Materials and Methods:This study was performed on formalin fixed and paraffin embedded tissue specimens with a diagnosis of invasive breast carcinoma archived at one university hospital in Isfahan city, Iran. We used imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Various studies have reported the EBV association with prognostic parameters in BC and have found EBV positivity to be associated with aggressive features like larger tumor size high histological grade, ER negativity and higher proportion of metastatic lymph nodes . On the contrary, no significant association was reported by other authors …”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported the EBV association with prognostic parameters in BC and have found EBV positivity to be associated with aggressive features like larger tumor size high histological grade, ER negativity and higher proportion of metastatic lymph nodes . On the contrary, no significant association was reported by other authors …”
Section: Discussionmentioning
confidence: 99%
“…Such evidence may provide opportunities for the pathogenesis, early detection and prevention of breast cancer (5,58,59). In particular, along with the reports of worse prognosis of EBV DNA positive patients than the negative patients (12,34,37), this can be applied to the treatment of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…While PCR shows a high sensitivity and specificity for the detection methods (5), Immunohistochemistry (IHC) shows a low degree of accuracy (17). Therefore, the two case-control studies adopting the IHC method (34,35) were excluded from the selection of studies for SR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations